Association between energy drink consumption, and substance use among adolescents: a cross sectional study - Nabulsi, Maisa; Ahmead, Muna (Frontiers in Nutrition, 2025)
BackgroundEnergy drinks (ED), which contain high doses of caffeine, are becoming increasingly popular, particularly among young people who may be unaware of the potential risks involved. The purpose of this study was to determine the prevalence of energy drink consumption among 12th-grade students, as well as the relationship between it and substance use, smoking, alcohol, depression, and anxiety.MethodsThe study utilized a cross-sectional research approach. Data was collected using a self-reported questionnaire that included sociodemographic data, substance use-related questions, smoking and drinking factors, and the Hospital Anxiety and Depression Scale (HADS).ResultsA total of 1,083 12th-grade students were recruited, revealing a high prevalence of energy drink consumption among them (52.5%). Also, the findings showed that participants whose father’s education was more than 12 years (AOR: 1.652, p < 0.001), participants who smoked cigarettes (AOR: 2.240, p < 0.004), participants who drank alcohol (AOR: 2.374, p < 0.005), and students who used waterpipe tobacco smoking (AOR: 5.401, p < 0.001) were more likely to drink energy drinks. No association was found between energy drinks and substance use.ConclusionOur study found that energy drink consumption is high among 12th-grade students, particularly those who smoke cigarettes, use waterpipe tobacco, or drink alcohol. Our findings highlight the pressing need to raise youth awareness and educate them about the negative health consequences of energy drink consumption.